A survey of 460 supernumerary teeth in Brazilian children and adolescents - CARLOS DE OLIVEIRA GOMES (IAPD and Blackwell, 2008)
Supernumerary teeth (ST) are described as those formed additionally to the normal dentition 1,2 . They have been found in both permanent and primary dentition, although less commonly in the latter 1,3,4 . The aetiology of ST is not completely understood and several theories have been proposed to explain their development 5 . ST could develop from a dichotomy of the tooth bud